Improving the photocatalytic performance of a sea-cucumber-like nanoporous TiO2 loaded with PtAg for water splitting. (21st May 2019) - Shi, Wenyu; Duan, Dong; Wang, Haiyang; Ma, Chen; Sun, Zhanbo; Song, Xiaoping
Abstract: Nanoporous TiO2 loaded with Pt and Ag was prepared by the dealloyed AlTiAgPt ribbons. The hydrogen generation rate via water splitting was measured for the photocatalytic performance. X-ray photoelectron spectroscopy (XPS), photoluminescence spectroscopy (PL), UV–vis diffuse reflectance spectroscopy (UV–vis) and Raman spectroscopy were employed to analyze the synergy among TiO2, Pt and Ag. The results indicate that the synthetic TiO2 shows an anatase structure and that the size of the Pt-rich phase, Ag and Ag-rich phase particles are approximately 6–8 nm. An abundance of pores with about 5 nm in size are distributed on the surface of TiO2, and obtained samples exhibit a larger specific surface area. The hydrogen evolution rate was approximately 1.85 mmol/h/g under full-spectrum irradiation for the dealloyed Al92 Ti7.86 Pt0.04 Ag0.1 ribbons, which was greatly improved compared with that of the dealloyed Al92 Ti7.9 Ag0.1 ribbons. The analyses indicate that Ag could promote the visible light absorption and that Pt serves as an electron sink for the effective electron-hole pairs separation. Moreover, the appropriate Schottky barrier, formed among the Pt-rich phase, Ag-rich phase and TiO2, effectively suppresses the recombination of electron-hole pairs and improves the utilization of photo-generated electrons. Graphical abstract: Image 1 Highlights: Sea cucumber-like PtAg/TiO2 composites exhibit a larger specific surface. Bimetal PtAg nanoparticles are uniformly distributed on the surface of TiO2 . The appropriate Schottky barrier effectively suppresses the recombination of e − -h + . Utilizing bimetal virtues is a novel scheme for photocatalytic performance. Bimetal PtAg/TiO2 nanocomposites exhibit the superior photocatalytic performance.